2019
DOI: 10.1002/lt.25346
|View full text |Cite
|
Sign up to set email alerts
|

Differing Impact of Sarcopenia and Frailty in Nonalcoholic Steatohepatitis and Alcoholic Liver Disease

Abstract: Sarcopenia and frailty are commonly encountered in patients with end‐stage liver disease and are associated with adverse clinical outcomes, including decompensation and wait‐list mortality. The impact of these entities in patients with differing disease etiologies has not been elucidated. We aim to ascertain the change in their prevalence over time on the wait list and determine their impact on hospitalization, delisting, and wait‐list survival, specifically for patients with nonalcoholic steatohepatitis (NASH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 23 publications
2
86
2
Order By: Relevance
“…Contrary to the current study, where lower KPSS was seen in patients with ALD, two other recent studies utilizing other assessment tools have reported that the underlying liver disease most associated with frailty is in fact NASH [9,10]. One of these studies objectively assessed frailty and functional status using hand grip, timed chair stands, and balance testing.…”
contrasting
confidence: 86%
See 1 more Smart Citation
“…Contrary to the current study, where lower KPSS was seen in patients with ALD, two other recent studies utilizing other assessment tools have reported that the underlying liver disease most associated with frailty is in fact NASH [9,10]. One of these studies objectively assessed frailty and functional status using hand grip, timed chair stands, and balance testing.…”
contrasting
confidence: 86%
“…The second study employed the Rockwood frailty index, which evaluates subjective and objective variables, showed that while frailty was more common in NASH, sarcopenia (using radiologic muscle assessment) was more common in ALD. With multivariate analysis, neither frailty nor sarcopenia among ALD patients impacted delisting [10]. These observations validate the aforementioned concerns about the limited reliability of KPSS.…”
supporting
confidence: 73%
“…In conclusion, the current study by Bhanji et al underscores the importance of muscularity and frailty assessment as part of LT assessment, in order to better predict outcomes in patients with cirrhosis. However, prospective longitudinal studies with a larger number of patients are required to overcome the obstacles in our current understanding of the predictive value of sarcopenia and frailty in patients with various etiologies of cirrhosis.…”
Section: Frequencies Of Sarcopenia and Frailty According To Etiologymentioning
confidence: 68%
“…(5) Standardized techniques are required to diagnose and manage sarcopenia and frailty in LT patients at initial and serial assessments.Cirrhosis due to nonalcoholic steatohepatitis (NASH) and alcoholic liver disease (ALD) are now the most common indications for LT. Despite this, there has been a lack of information about the risk factors and implications in patients with a diagnosis of NASH or ALD (Table 1).In this issue of Liver Transplantation, Bhanji et al (9) address this issue by evaluating 136 patients with NASH and 129 with ALD-related cirrhosis. The prevalence of sarcopenia, as analyzed by computed tomography (CT) scan, was lower in patients with NASH (22% versus 47%; P < 0.001) but with a considerably higher frequency of frailty, which was defined using the frailty deficit index (49% versus 34%; P = 0.03) when compared with patients with ALD at the time of listing.…”
mentioning
confidence: 99%
“…Patients may require a liver transplant once they develop decompensated cirrhosis, hepatocellular carcinoma (HCC) or certain other complications of cirrhosis. NASH patients with cirrhosis may also develop sarcopenia and frailty, which can worsen their waiting list mortality . After liver transplantation, these patients must take diabetogenic medications such as steroids, tacrolimus and mammalian target of rapamycin inhibitors to prevent allograft rejection because of their increased metabolic risk.…”
Section: Managing Patients With Cirrhosis and Nashmentioning
confidence: 99%